Vojteh Ribnikar in poslanstvo šolskega vrta - Orešnik, Urška (Šolska kronika, 2015)
Vojteh Ribnikar was more than a teacher. He was a man who saw his work as his mission in life. His aim was to not merely teach, but to prepare his students fully for life, and he regarded the school garden, where he could teach his students useful and practical skills, as a means of achieving this. Based on his practical experience, Mr. Ribnikar also designed a curriculum for agriculture and fruit growing in primary schools to recommend these activitiesto his colleagues. In addition to his contribution to education in Slovenia in general, his broader activities also contributed towards the development of the entire Logatec region - for which he is still remembered by its inhabitants today.
Keywords: 1878-1895; 19.st.; biografije; Dolnji Logatec; history; Logatec; osnovne šole; Ribnikar, Vojteh, 1857-1895; sadjarstvo; school; šolski vrtovi; Šolstvo; učitelji; Vrtovi; Zgodovina